Mechanical characteristics of roll crushing of ore materials based on discrete element method - Ruijie Gu; Zhenzhong Qin; Shuaifeng Zhao; Hao Xing; Liaoyuan Chen; Fang Yang (Scientific Reports)
Abstract The application of high-pressure grinding rolls (HPGR) for ore crushing is considered to be one of the effective ways to save energy and reduce emissions in the ore processing industry. The crushing effect is directly determined by the forces of ore material during roll crushing. However, the mechanical state of ore material in roll crushing and the effect of roll structure, process parameters, feed particle size, on the force during the crushing of ore material needs to be expanded. Therefore, this paper intends to use the discrete element method to study the mechanical characteristics of roll crushing of ore materials. Firstly, the iron ore breakage model parameters are calibrated according to compression and impact crushing tests. Then, considering different roll structures, process parameters, and feed particle sizes of high-pressure grinding rolls, a simulation of the industry high-pressure grinding roll crushing process is developed. The particle velocity is innovatively used to study the force of particles in different regions of the compression zone. Considering the force and wear of ore particles, rollers, and cheek plates, the breakage process of HPGR is analyzed comprehensively. The results show that the material in the roll-crushing process is mainly subject to the normal force. The forces on particles at different locations in the compression zone are related to average velocity. To improve the crushing effect of HPGR, the crushing process of the ore should be combined with the wear of the roller and cheek plates. The vulnerable zone between the roller and cheek plates is indicated, and the extrusion pressure of the roller is slightly lower than the shear force between the particles.